Legal Protection for Children Exploited as Beggars in Bandar Lampung City - M. Rizki Fatulloh; Rinaldy Amrullah; Rini Fathonah; Muhtadi Muhtadi (Yayasan Kawanad, 2025)
Child exploitation through forced begging in Bandar Lampung City constitutes a severe violation of fundamental rights, substantially undermining both physical and psychological development. Criminal networks systematically manipulate vulnerable minors for economic gain, representing a grave breach of child labor protection statutes. This research examines law enforcement mechanisms targeting exploitation perpetrators, identifies systemic barriers, and proposes enhanced legal protection frameworks. The investigation employs a sociological-juridical methodology, utilizing documentary analysis, ethnographic observations, and structured interviews with law enforcement personnel, social service practitioners, and child advocacy specialists. Analysis draws upon child protection theory and progressive jurisprudence principles. Findings reveal enforcement mechanisms remain fragmented, reactive, and institutionally unsupported. Primary impediments encompass inter-agency coordination deficits, inadequate street children documentation, and insufficient rehabilitation funding. The research advocates for policy restructuring and systematic strengthening of child protection mechanisms through interdisciplinary collaboration. The study's significance lies in advancing more integrated and effective legal safeguards for exploited children across municipal and national jurisdictions.